DATA MODELS IN INFORMATION TECHNOLOGY - RAVI TEJA YARLAGADDA (International Journal of Innovations in Engineering Research and Technology, 2016)
Information technology involves an enormous amount of data sources dispersed over computer networks. The assortment of data sources and differences of interfaces makes the undertaking of effectively finding and proficiently getting to data over the network unwieldy. We portray a design for worldwide data frameworks that are particularly custom-made to address such a condition's difficulties. Our design depends on introducing a reasonably bound together perspective on the data model to a client, specifying the model's kind to be utilized by a specific organization reliant upon the accessible assets and the purpose of the model.